Evaluation of Growth Performance, Carcass Characteristics, Digestibility and Ileum Histomorphology of Broiler Chickens fed Two Forms of Diets Supplemented with Exogenous Proteases - RA Alhotan; HH Al-Baadani; EOS Hussein (Brazilian Journal of Poultry Science)
ABSTRACT The aim of this study was to evaluate the effects of diets supplemented with exogenous proteases on the performance, carcass characteristics, digestibility and histomorphology of broilers. A total of 1,536 male broilers (one day old) were used for the study. All broilers were divided into 96 floor pens with 16 chicks each. The dietary treatments were as follows: A= basal diet; B= basal diet + 0.02% RelePro (alkaline, acidic, and neutral proteases), C= basal diet + 0.03% Kemzyme (multiproteases), and D=basal diet + 0.02% ProAct (protease-derived Bacillus licheniformis). They were fed in two forms of diets (mash or pelleted) in a 4x2 factorial design. Growth performance and carcass traits were evaluated. The digestibility of dry matter and crude protein were measured, as well as histomorphological parameters. The results showed that birds in the C and D groups in pelleted form had a higher body weight, production and performance index, and better feed conversion ratio. Chickens fed a pelleted diet with protease C, followed by proteases B and D, and chickens fed a diet mashed with protease C had a higher digestibility of dry matter and crude protein. Animals in the group receiving protease B in the pelleted diet had a higher crypt depth. Chickens fed pelleted diet with protease C had higher villus height to crypt depth ratio and goblet cells. The live weight and relative weight of the breast increased, and the relative weights of the wings decreased with pelleted diet. In conclusion, the use of protease had positive effects on growth performance, dry matter and crude protein digestibility, and ileum histomorphological parameters without negatively affecting carcass characteristics, which was more evident when feeding a pelleted diet to broilers.